Studi Sistematis Hadis Keutamaan Hidup Bertetangga - Silmi Mutakiah; Wahyudin Darmalaksana (Gunung Djati Conference Series, 2022)
This study aims to discuss the hadith about neighborly life. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about neighborly life in the history of Bukhari no. 5994. The results and discussion of this study indicate that the quality of the hadith is considered authentic with the status of maqbul ma'mul bih for the practice of Islam in strengthening neighborly life. This study concludes that the hadith narrated by Bukhari no. 2262 is relevant to be used as the design of an extension model on the virtues of neighborly living in the context of Indonesian society.